Management of The Cervical Spine Tuberculosis - Sabri Ibrahim (Indoscholar, 2018)
Tuberculosis of the cervical spine is a rare clinical condition (10%), most commonly affected lower thoracic region (40-50% of the cases). Spinal tuberculosis is a destructive form of tuberculosis. It accounts for approximately half of all cases of musculoskeletal tuberculosis. Spinal tuberculosis is more common in children and young adults. The incidence of spinal tuberculosis is increasing in developed nations. Characteristically, there is a destruction of the intervertebral disk space and the adjacent vertebral bodies, collapse of the spinal elements, and anterior wedging leading to kyphosis and gibbus formation. For the diagnosis of spinal tuberculosis, magnetic resonance imaging is more sensitive than x-ray and more specific than computed tomography. Magnetic resonance imaging frequently demonstrates an involvement of the vertebral bodies on either side of the disk, disk destruction, cold abscess, vertebral collapse, and presence of vertebral column deformities. Anti-tuberculous treatment remains the cornerstone of treatment. Surgery may be required in selected cases, e.g. large abscess formation, severe kyphosis, an evolving neurological deficit, or lack of response to medical treatment. The quality of debridement and bony fusion is optimal when the anterior approach is used. Posterior fixation is the best means of achieving reduction followed by stable sagittal alignment over time. With early diagnosis and early treatment, the prognosis is generally good.